0

# IF 2 plus 3 equals 10 7 plus 2 equals 63 6 plus 5 equals 66 8 plus 4 equals 96 THEN 9 plus 7 equals?

Updated: 9/15/2023

Wiki User

13y ago

The compound operator for (a) and (b) in each pair is a * (a+b).

For 9 and 7, this is 9 x (9+7) = 9 x 16 = 144.

Wiki User

13y ago

Earn +20 pts
Q: IF 2 plus 3 equals 10 7 plus 2 equals 63 6 plus 5 equals 66 8 plus 4 equals 96 THEN 9 plus 7 equals?
Submit
Still have questions?
Related questions

26

96

144

144

### 2 plus 3 equals 10. 7 plus 2 equals 63. 6 plus 5 equals 66. 8 plus 4 equals 96. 9 plus 7 equals?

144 add the two numbers and multiply by the first 2(2 + 3) = 10 7(7 + 2) = 63 etc.

### 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 Then 9 plus 7 equals?

If I am correct, 9 plus 7 equals 112.

### 2 plus 3 equals 10 7 plus 2 equals 63 6 plus 5 equals 66 8 plus 4 equals 96 9 plus 7 equals?

144, you add the plus numbers, then multiply it by the first.

### If 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 what does 9 plus 7 equals?

144, you add the plus numbers, then multiply it by the first.

### If 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 Then 9 plus 7 equals what?

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

### If 2 plus 3 equals 10 and 7 plus 2 equals 63 and 6 plus 5 equals 66 and 8 plus 4 equals 96 then what does 9 plus 7 equals?

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

### What does 9 plus 7 equals if 2 plus 3 equals 10 7 plus 2 equals 63 6 plus 5 equals 66 8 plus 4 equals 96?

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.